Chaotic Structure of Oil Prices - Bildirici, Melike; Sonustun, Fulya Ozaksoy (AMER INST PHYSICS, 2018)
The fluctuations in oil prices are very complicated and therefore, it is unable to predict its effects on economies. For modelling complex system of oil prices, linear economic models are not sufficient and efficient tools. Thus, in recent years, economists attached great attention to non-linear structure of oil prices. For analyzing this relationship, GARCH types of models were used in some papers. Distinctively from the other papers, in this study, we aimed to analyze chaotic pattern of oil prices. Thus, it was used the Lyapunov Exponents and Hennon Map to determine chaotic behavior of oil prices for the selected time period.
Keywords: Oil price; BDS test; Lyapunov Exponent; Chaos; Non-linearity; SMOOTH TRANSITION; Mathematics